Scientometric analysis of twenty years of research on school-to-work transition - Oetomo, Gempita Sari; Abdullah, Ade Gaffar; Haritman, Erik (INVOTEC, 2023)
The suitability of work in adolescents with education graduates is very important, to explore the role of learning and skill skills in the process of transitioning from education to the world of work with results that show more dominance in theoretical knowledge, communication, problem-solving, and learning abilities. The transition from education to the world of work is marked by conditions that are constantly changing and the stability of education is starting to diminish. This study analyzes the most relevant themes related to the transition from education to the world of work through scientometric analysis using the keywords “School-to-Work Transition”, “S2W” and “Transition” as input. The Scopus database is used because it is considered the largest and most trusted database for scientometric analysis. VOSviewer software was adopted as a scientometric analysis tool for network mapping based on author, country, source, keywords, and latest discoveries. The analysis conducted on March 1 2022, found a total of 726 documents in the period 2001 to 2021 of STWT research with filtered articles in English. The results of this study indicate that in the last twenty years the number of publications on STWT has grown significantly. Based on the findings of this analysis, studies on STWT in the last four years have focused on themes related to unemployed youth, education and training, early school leave, and the country of Italy. Along with the times and increasingly sophisticated technology, a researcher requires to have innovations that are useful for further research